Mendekolonisasi Agama: Melibatkan Pengetahuan Masyarakat Adat dan Praktik Teologi Transformatif di Tengah Ketidakstabilan Global - Muwahidah, Siti Sarah (Reformed Center for Religion and Society, 2025)
The perceived binary between “world religions” and indigenous traditions is a colonial construct. The editorial asserts that dismantling this oppositional framework is essential for decolonizing religion and enabling constructive conversations with local and indigenous episteme and practices. The five articles in this edition demonstrate how engaging with local practices and indigenous knowledge creates space for resilience, relationality, and ecological stewardship. Such a decolonial approach offers a crucial framework for responding to contemporary global problems, including the climate crisis, economic precarity, and systemic injustices. Ultimately, this editorial calls for more holistic religious praxes and alternative socio-ethical imaginaries.